Inorganic material, preparation method and application thereof, diaphragm and lithium ion battery
By preparing and applying the inorganic material Li6.55GaxAlyFezLa3Zr2O12, the problems of poor wetting and separator shrinkage in liquid lithium-ion batteries are solved, improving battery safety and reducing costs.
Patent Information
- Application Number
- CN202310762222.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
There are safety problems with liquid lithium-ion batteries, mainly due to poor wetting properties of the diaphragm and electrolyte and the short circuit of the positive and negative electrodes caused by the shrinkage of the diaphragm.
Provided an inorganic material Li6.55GaxAlyFezLa3Zr2O12, prepared by mixing lithium, lanthanum, zirconium, aluminum, iron and gallium sources and ball milling, roasting and calcining, to be used for the separator of lithium-ion batteries to improve the contact between the base film and the electrolyte. Angle and surface tension improve wettability of the diaphragm and electrolyte and inhibit diaphragm shrinkage.
It effectively improves the wetting properties of the diaphragm and electrolyte, reduces the shrinkage of the diaphragm, improves battery safety, and reduces costs.
Smart Images

Figure CN119191361A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to an inorganic material and a preparation method and application thereof, a diaphragm and a lithium ion battery. Background Art
[0002] Li7La3Zr2O 12 (LLZO) is an inorganic material widely used in lithium-ion batteries. LLZO-based powder has the advantage of high ionic conductivity. In all-solid-state lithium-ion batteries, it can be used in solid electrolytes, inorganic-organic composite diaphragms, polymer film coatings, positive electrode material coatings, and negative electrode material ionic conductive agents. Based on the versatility of LLZO materials, it is of great value to expand LLZO-based products.
[0003] At present, there are safety issues in liquid lithium-ion batteries, mainly due to the poor wettability of the diaphragm and the electrolyte and the short circuit of the positive and negative electrodes caused by the shrinkage of the diaphragm. Therefore, it is of great significance to expand LLZO materials, explore their applications in lithium-ion batteries, improve battery safety, improve the wettability of the diaphragm and the electrolyte, and inhibit the shrinkage of the diaphragm. Summary of the invention
[0004] The present invention is based on the inventor's discovery and understanding of the following facts and problems: Liquid lithium-ion batteries have safety issues, mainly due to poor wettability between the diaphragm and the electrolyte and the shrinkage of the diaphragm causing a short circuit between the positive and negative electrodes. Therefore, it is of great significance to expand LLZO materials, explore their application in lithium-ion batteries, improve battery safety, improve the wettability of the diaphragm and the electrolyte, and inhibit the shrinkage of the diaphragm.
[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides an inorganic material, the chemical formula of which is Li 6.55 Ga x Al y Fe z La3Zr2O 12 , where 0 <x<0.15,0<y<0.15,0<z<0.15,x+y+z=0.15。
[0006] Optional, 0.03≤x≤0.1, 0.04≤y≤0.07, 0.01≤z≤0.05.
[0007] Optionally, the inorganic material includes Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 , Li 6.55 Ga 0.05Al 0.05 Fe 0.05 La3Zr2O 12 , Li 6.55 Ga 0.03 Al 0.07 Fe 0.05 La3Zr2O 12 At least one of .
[0008] Optionally, the inorganic material is of garnet type; preferably, the inorganic material is of tetragonal phase structure.
[0009] Optionally, the particle size of the inorganic material is 50 nm to 800 nm, preferably 300 nm to 600 nm.
[0010] Optionally, the space group of the crystal structure of the inorganic material is I41 / acd; preferably, the unit cell parameter of the crystal structure of the inorganic material is
[0011] The present invention provides a method for preparing an inorganic material, comprising the following steps:
[0012] (1) mixing a lithium source, a lanthanum source, a zirconium source, an aluminum source, an iron source, and a gallium source, adding a solvent, and ball milling to obtain a mixed slurry;
[0013] (2) drying the mixed slurry obtained in step (1), and then roasting it, and then calcining it to obtain an inorganic material; wherein the calcination temperature is higher than the roasting temperature.
[0014] Optionally, in step (1), the lithium source includes LiOH·H2O; the lanthanum source includes La2O3; the zirconium source includes ZrO2; the aluminum source includes Al2O3; the iron source includes Fe2O3; and the gallium source includes Ga2O3;
[0015] And / or, in the step (1), the ball milling time is 3 to 5 hours;
[0016] And / or, in the step (2), the calcination temperature is 600-700° C., and the calcination time is 1-2 h;
[0017] And / or, in the step (2), the calcination temperature is 900-1000° C., and the calcination time is 2-7 hours.
[0018] The present invention provides an application of an inorganic material, wherein the inorganic material is used in a lithium ion battery;
[0019] And / or, the inorganic material is used for at least one of a solid electrolyte, a separator, a membrane coating, a positive electrode material coating layer or a negative electrode material ion conductor.
[0020] The present invention provides a separator including the inorganic material.
[0021] The present invention provides a method for preparing a separator, comprising the following steps:
[0022] 1) Mix the inorganic material, binder and solvent to obtain a slurry;
[0023] 2) Coat the slurry on one or both sides of a base film and dry to obtain the separator.
[0024] The present invention provides a lithium-ion battery including the inorganic material or the separator.
[0025] According to the inorganic material provided by the present invention, the chemical formula of the inorganic material is Li 6.55 Ga x Al y Fe z La3Zr2O 12 , which contains Ga, Al, and Fe elements and can effectively promote the stability of the crystal structure of the inorganic material and regulate the microscopic crystal structure and lithium-ion transport channels of the material. Among them, 0 < x < 0.15, 0 < y < 0.15, 0 < z < 0.15, and x + y + z = 0.15, so that an inorganic material with a tetragonal phase structure can be obtained while maintaining the effective lithium-ion transport amount of the inorganic material. The inorganic material Li 6.55 Ga x Al y Fe z La3Zr2O 12 can improve the contact angle between the base film and the electrolyte, reduce the surface tension, effectively improve the wettability of the separator with the electrolyte. Compared with the blank base film, the separator coated with the inorganic material has better heat resistance, thereby inhibiting the shrinkage of the separator, improving the battery safety and reducing the cost.
[0026] Mix a lithium source, a lanthanum source, a zirconium source, an aluminum source, an iron source, and a gallium source, add a solvent, and ball mill to obtain a mixed slurry. Wet ball milling can effectively promote the full contact between different raw materials and avoid the local enrichment of a single material; then the mixed slurry is dried and then calcined to achieve a low-temperature pre-reaction of some target products, facilitating the smooth progress of the high-temperature reaction; after calcination, it is sintered, and the sintering temperature is higher than the calcination temperature and is the effective kinetic reaction temperature of the target material to obtain the inorganic material. The inorganic material can effectively improve the wettability of the separator with the electrolyte, inhibit the shrinkage of the separator, improve the battery safety and reduce the cost. Description of the Drawings
[0027] Figure 1 is Li in Example 1 6.55 Ga 0.1 Al 0.04 Fe0.01 La3Zr2O 12 X-ray powder diffraction pattern of
[0028] Figure 2 is Li in Example 1 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 morphology and structure of the powder Detailed implementation manners
[0029] The embodiments of the present invention will be described in detail below. The examples of the embodiments are shown in the accompanying drawings. The embodiments described below by referring to the accompanying drawings are exemplary and are intended to explain the present invention, and should not be construed as a limitation to the present invention.
[0030] An inorganic material according to an embodiment of the present invention, the chemical formula of the inorganic material is Li 6.55 Ga x Al y Fe z La3Zr2O 12 , where 0 < x < 0.15, 0 < y < 0.15, 0 < z < 0.15, and x + y + z = 0.15.
[0031] The chemical formula of the inorganic material is Li 6.55 Ga x Al y Fe z La3Zr2O 12 , containing Ga, Al, and Fe elements, can effectively promote the stability of the crystal structure of the inorganic material and regulate the microscopic crystal structure and lithium ion transport channels of the material. Among them, 0 < x < 0.15, 0 < y < 0.15, 0 < z < 0.15, and x + y + z = 0.15, an inorganic material with a tetragonal phase structure can be obtained while maintaining the effective lithium ion transport amount of the inorganic material. The inorganic material Li 6.55 Ga x Al y Fe z La3Zr2O 12 can improve the contact angle between the base film and the electrolyte, reduce the surface tension, can effectively improve the wettability of the separator and the electrolyte. Compared with the blank base film, the separator coated with the inorganic material has better heat resistance, thereby inhibiting the shrinkage of the separator, improving the battery safety, and reducing the cost.
[0032] In specific embodiments, x can be 0.01, 0.03, 0.05, 0.07, 0.09, 0.10, 0.11, 0.13, 0.14, y can be 0.01, 0.03, 0.04, 0.05, 0.07, 0.09, 0.10, 0.11, 0.13, 0.14, and z can be 0.01, 0.03, 0.05, 0.07, 0.09, 0.10, 0.11, 0.13, 0.14.
[0033] In a preferred embodiment, 0.03≤x≤0.1, 0.04≤y≤0.07, and 0.01≤z≤0.05.
[0034] In a specific embodiment, the inorganic material includes Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 , Li 6.55 Ga 0.0 5Al 0.05 Fe 0.05 La3Zr2O 12 , Li 6.55 Ga 0.03 Al 0.07 Fe 0.05 La3Zr2O 12 At least one of .
[0035] In the embodiment of the present invention, the inorganic material is preferably Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 , Li 6.55 Ga 0.05 Al 0.05 Fe 0.05 La3Zr2O 12 , Li 6.55 Ga 0.03 Al 0.07 Fe 0.05 La3Zr2O 12 , which can further improve the wettability of the diaphragm and the electrolyte, further inhibit the shrinkage of the diaphragm, and further improve the safety of the battery.
[0036] In some embodiments, the inorganic material is garnet-type;
[0037] Preferably, the inorganic material has a tetragonal phase structure;
[0038] More preferably, the space group of the crystal structure of the inorganic material is I41 / acd (No.142); the unit cell parameter of the crystal structure of the inorganic material is
[0039] In the embodiment of the present invention, when x+y+z≠0.15, the inorganic material with a tetragonal structure cannot be effectively prepared. By preferably using the inorganic material with a tetragonal structure, relatively mild preparation conditions and lower raw material costs can be achieved. At the same time, the inorganic material with a tetragonal structure has a higher lithium ion conductivity, which is beneficial to reducing the development cost of the material and improving the application performance.
[0040] In some embodiments, the particle size of the inorganic material is 50 nm to 800 nm, preferably 300 nm to 600 nm.
[0041] In specific embodiments, the particle size is 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm.
[0042] The method for preparing the inorganic material according to the embodiment of the present invention comprises the following steps:
[0043] (1) mixing a lithium source, a lanthanum source, a zirconium source, an aluminum source, an iron source, and a gallium source, adding a solvent, and ball milling to obtain a mixed slurry;
[0044] (2) drying the mixed slurry obtained in step (1), and then roasting it, and then calcining it to obtain an inorganic material; wherein the calcination temperature is higher than the roasting temperature.
[0045] In the embodiment of the present invention, lithium source, lanthanum source, zirconium source, aluminum source, iron source and gallium source are mixed, solvent is added, ball milling is performed to obtain a mixed slurry, and wet ball milling can effectively promote full contact between different raw materials and avoid local enrichment of a single material; then the mixed slurry is dried and roasted to achieve low-temperature pre-reaction of part of the target product, which is convenient for the smooth progress of high-temperature reaction; after roasting, calcination is performed, and the calcination temperature is higher than the roasting temperature, which is the effective kinetic reaction temperature of the target material, to obtain the inorganic material. Inorganic materials can effectively improve the wettability of the diaphragm and the electrolyte, inhibit the shrinkage of the diaphragm, improve battery safety and reduce costs.
[0046] In some embodiments, in step (1), the lithium source includes LiOH·H2O; the lanthanum source includes La2O3; the zirconium source includes ZrO2; the aluminum source includes Al2O3; the iron source includes Fe2O3; the gallium source includes Ga2O3;
[0047] And / or, in the step (1), the lithium source, lanthanum source, zirconium source, aluminum source, iron source and gallium source are mixed according to the stoichiometric ratio in the chemical formula of the inorganic material;
[0048] And / or, in the step (1), the ball milling time is 3 to 5 hours, specifically, for example, 3 hours, 4 hours, 5 hours; the ball milling speed is 400 to 800 rpm, specifically, for example, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm;
[0049] And / or, in step (1), the solvent is isopropanol;
[0050] And / or, in the step (2), the drying is carried out by oven drying;
[0051] And / or, in the step (2), the calcination temperature is 600-700°C, specifically, for example, 600°C, 650°C, 700°C; the calcination time is 1-2h, specifically, for example, 1h, 1.5h, 2h;
[0052] And / or, in the step (2), the calcination temperature is 900-1000°C, specifically, for example, 900°C, 950°C, 1000°C; the calcination time is 2-7h, specifically, for example, 2h, 3h, 4h, 5h, 6h, 7h.
[0053] In some embodiments, the prepared inorganic material is further refined to obtain an inorganic material with a target particle size. The refinement equipment used in the refinement includes at least one of a ball mill and a sand mill.
[0054] Application of the inorganic material of the embodiment of the present invention or the inorganic material prepared by the preparation method of the embodiment of the present invention, wherein the inorganic material is used in a lithium ion battery;
[0055] And / or, the inorganic material is used for at least one of a solid electrolyte, a separator, a membrane coating, a positive electrode material coating layer or a negative electrode material ion conductive agent. In the embodiment of the present invention, all the advantages of the inorganic material of the present invention are possessed, which will not be described in detail here.
[0056] In some embodiments, the membrane coating includes a membrane coating and / or other polymeric membrane coating.
[0057] A diaphragm according to an embodiment of the present invention comprises an inorganic material according to an embodiment of the present invention or an inorganic material prepared by a preparation method according to an embodiment of the present invention. 6.55 Ga x Al y Fe z La3Zr2O 12Applied to battery separators, it can effectively improve the wettability of the separators with electrolytes, inhibit separator shrinkage, improve battery safety and reduce costs.
[0058] In some embodiments, the separator includes a base film and a coating layer on one side or both sides of the base film, and the coating layer contains the inorganic material.
[0059] In some embodiments, the base film is a polyolefin base film.
[0060] In some embodiments, the polyolefin-based film includes at least one of a polypropylene (PP)-based film and a polyethylene (PE)-based film.
[0061] In some embodiments, the base film has a thickness of 9 to 12 μm, specifically, for example, 9 μm, 10 μm, 11 μm, 12 μm.
[0062] In some embodiments, the thickness of the single-sided coating layer is 1 to 6 μm, specifically, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm.
[0063] The method for preparing the diaphragm according to the embodiment of the present invention comprises the following steps:
[0064] 1) mixing the inorganic material, the binder and the solvent to obtain a slurry;
[0065] 2) The slurry is coated on one side or both sides of a base film and dried to obtain a separator.
[0066] The embodiments of the present invention have all the advantages of the inorganic material or membrane of the present invention, which will not be described in detail here.
[0067] In some embodiments, in step 1), the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, modified styrene-butadiene rubber, polyurethane, sodium carboxymethyl cellulose, polyvinyl alcohol or polyacrylate copolymer latex;
[0068] And / or, the binder comprises a copolymer of polyvinylidene fluoride and a monomer compound, wherein the monomer compound contains at least one of an amine group, an epoxy group, a carboxyl group, a thioether group, and a carboxylic anhydride group;
[0069] And / or, the mass ratio of the inorganic material to the binder is 100:0.1-2, specifically, for example, 100:0.1, 100:1, 100:2;
[0070] and / or, the solvent comprises at least one of N-methylpyrrolidone (NMP), dichloromethane, and xylene;
[0071] And / or, the mixing is carried out by stirring, and the mixing time is 1 to 48 hours, specifically, for example, 1 hour, 6 hours, 12 hours, 24 hours, 48 hours.
[0072] In some embodiments, in step 2), the drying is performed by vacuum drying; the drying temperature is 50-80°C, specifically, for example, 50°C, 60°C, 70°C, 80°C; the drying time is 6-48h, specifically, for example, 6h, 12h, 24h, 48h.
[0073] The present invention provides a lithium ion battery, comprising an inorganic material according to an embodiment of the present invention or an inorganic material prepared by a preparation method according to an embodiment of the present invention or a diaphragm according to an embodiment of the present invention or a diaphragm prepared by a preparation method according to an embodiment of the present invention. In the embodiment of the present invention, all the advantages of the inorganic material or diaphragm according to the present invention are possessed, which will not be described in detail here.
[0074] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0075] Embodiment 1:
[0076] A method for preparing a high-safety lithium-ion battery comprises the following steps:
[0077] (1) Positive electrode: The ternary material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black Super P, carbon nanotubes, and polyvinylidene fluoride are mixed in a ratio of 93:2.5:2:2.5, and 50% by weight of the above powders of NN-dimethylpyrrolidone are added and stirred evenly to form a positive electrode slurry, and the positive electrode slurry is evenly coated on a 16 μm thick aluminum foil, and after drying, it is rolled with a rolling machine to make a positive electrode sheet;
[0078] (2) Negative electrode sheet: artificial graphite, conductive carbon black super P, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a ratio of 94:2:1.7:2.3, and 80% by weight of deionized water of the above powders is added and stirred evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on a 10 μm thick negative electrode current collector copper foil, and after drying, it is rolled using a roller to form a negative electrode sheet;
[0079] (3) Prepare the diaphragm: The diaphragm is a microporous composite diaphragm with a thickness of 9+2+2 μm, where 9 μm is the thickness of the PP base film and 2+2 is the thickness of the Li on both sides of the base film. 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12The thickness of the solid electrolyte coating layer is 2 μm, Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 The particle size of the solid electrolyte is 600nm;
[0080] The preparation method of the diaphragm is as follows:
[0081] Step 1: Tetragonal phase structure Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 Powder preparation:
[0082] LiOH·H2O powder, Ga2O3 powder, Al2O3 powder, Fe2O3 powder, La2O3 powder and ZrO2 powder were weighed and mixed according to the stoichiometric ratio in the chemical formula, and an appropriate amount of isopropanol solvent was added. The mixture was ball-milled in a planetary ball mill at a speed of 600 rpm for 4 hours. The ball-milled slurry was then dried and placed in a magnesium oxide crucible, and then placed in a muffle furnace and calcined at 650°C for 1 hour, and then calcined at 950°C for 6 hours to obtain a tetragonal Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 Powder. Tetragonal structure Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 The X-ray powder diffraction pattern and morphology of the powder are as follows: Figure 1 and 2 shown.
[0083] Step 2: Preparation of fine powder: Prepare Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 The powder was refined by ball mill to obtain Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 Powder material.
[0084] Step 3: Preparation of slurry: weigh 5g of binder polyvinylidene fluoride and 500g of Li 6.5 5Ga 0.1 Al0.04 Fe 0.01 La3Zr2O 12 The powder material was then added with 500 g of NMP solvent and stirred for 24 h to obtain a slurry;
[0085] Step 4: Slurry coating: Cut a polypropylene base film with a thickness of 9 μm and lay it flat on the coating machine, then pour the stirred slurry evenly on one side, and control the scraper to evenly coat the slurry on the polypropylene base film at a certain linear speed. After coating, put it in a vacuum drying oven and vacuum dry it at 60°C for 12 hours to obtain a composite diaphragm with a coating layer on one side; the other side is coated and dried in a similar manner to obtain a lithium-ion battery composite diaphragm.
[0086] (4) preparing an electrolyte: dissolving lithium hexafluorophosphate (LiPF6) in an organic solvent mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), wherein the weight ratio of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate is 1:1:1, and the concentration of the lithium hexafluorophosphate is 1.20 mol / L;
[0087] (5) Prepare the battery: stack the positive electrode sheet, separator, and negative electrode sheet alternately to form a battery cell, then heat-seal with aluminum-plastic film, inject electrolyte, and heat-seal the opening; and sequentially perform the steps of placing, forming, secondary sealing, and capacity separation to produce a 2Ah lithium-ion power battery.
[0088] Embodiments 2 to 6
[0089] Examples 2 to 6 are used to illustrate the lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0090] The composition and particle size of the tetragonal inorganic material of the solid electrolyte coating layer of the diaphragm used in Examples 2 to 6 are shown in Table 1.
[0091] Comparative Examples 1 to 3
[0092] Comparative Examples 1 to 3 are used to compare and illustrate the lithium ion battery disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0093] The composition and particle size of the solid electrolyte coating layer of the separator used in Comparative Examples 1 to 3 are shown in Table 1.
[0094] Performance Testing
[0095] The lithium-ion battery prepared above was subjected to the following performance tests:
[0096] 1. Thermal stability test:
[0097] The composite membrane obtained in step (3) is cut into a 2 cm × 2 cm square. After being placed at a certain temperature for 60 minutes, the area of the composite membrane is measured and compared with the initial area to calculate the shrinkage rate of the composite membrane after heat treatment.
[0098] Shrinkage rate = (S1-S2) / S1*100%, where S1 is the initial area and S2 is the area after heating for 1 hour.
[0099] 2. Liquid retention test:
[0100] Cut the diaphragm into 10cm*10cm square pieces, weighing m1; soak the pieces in electrolyte for 24h, take them out, drain the floating liquid, and weigh m2;
[0101] Liquid retention volume = (m2-m1) / area;
[0102] 3. Safety acupuncture performance test:
[0103] Take 10 of the prepared batteries and conduct a single battery puncture safety test.
[0104] The measurement method is as follows: charge a single battery to 100% SOC, and then use a steel needle with a diameter of 3 mm to vertically penetrate the center of the battery cell at a speed of 25 mm / min (the steel needle stays in the battery cell for 300 seconds).
[0105] The battery parameters and performance data of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Tables 1-3.
[0106] Table 1
[0107]
[0108]
[0109] Table 2
[0110]
[0111] It can be seen from Table 2 that compared with the diaphragm coated with Al2O3, the diaphragm coated with the inorganic material of the present invention has a lower shrinkage rate under the same temperature conditions, exhibits better high temperature resistance, can effectively improve the thermal shrinkage performance of the battery diaphragm, and improve battery safety.
[0112] Table 3
[0113] Group <![CDATA[Liquid retention amount (g / m 2 )]]> Acupuncture phenomenon Example 1 4.52 9 batteries caught fire without smoke, 1 battery caught fire with smoke Example 2 4.63 10 batteries did not smoke or catch fire, and 0 batteries smoked or caught fire Example 3 4.46 9 batteries caught fire without smoke, 1 battery caught fire with smoke Example 4 4.61 10 batteries did not smoke or catch fire, and 0 batteries smoked or caught fire Example 5 4.53 10 batteries did not smoke or catch fire, and 0 batteries smoked or caught fire Example 6 4.72 9 batteries caught fire without smoke, 1 battery caught fire with smoke Comparative Example 1 3.78 1 battery caught fire without smoke, 9 batteries caught fire with smoke Comparative Example 2 3.92 1 battery caught fire without smoke, 9 batteries caught fire with smoke Comparative Example 3 3.24 10 batteries smoked and caught fire
[0114] It can be seen from Table 3 that, compared with the diaphragm coated with Al2O3, the diaphragm coated with the inorganic material of the present invention has better liquid retention performance of the lithium ion battery, the wettability of the diaphragm with the electrolyte is improved, and the amount of electrolyte used can be effectively reduced.
[0115] For the safety needle puncture performance test, compared with the lithium ion battery containing the separator of Al2O3, the lithium ion battery containing the separator of the inorganic material of the present invention exhibits higher battery safety.
[0116] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0117] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. An inorganic material, characterized in that The chemical formula of the inorganic material is Li 6.55 Ga x Al y Fe z La3Zr2O 12 , where 0 <x<0.15,0<y<0.15,0<z<0.15,x+y+z=0.15。 2. The inorganic material according to claim 1, characterized in that 0.03≤x≤0.1, 0.04≤y≤0.07, 0.01≤z≤0.05; Preferably, the inorganic material comprises Li 6.55 Ga 0.1 Al 0.04 Fe 0.01 La3Zr2O 12 , Li 6.55 Ga 0.05 Al 0.05 Fe 0.05 La3Zr2O 12 , Li 6.55 Ga 0.03 Al 0.07 Fe 0.05 La3Zr2O 12 At least one of .
3. The inorganic material according to claim 1, characterized in that The inorganic material is of garnet type; preferably, the inorganic material is of tetragonal phase structure; And / or, the particle size of the inorganic material is 50nm to 800nm, preferably 300nm to 600nm.
4. The inorganic material according to claim 3, characterized in that The space group of the crystal structure of the inorganic material is I41 / acd; preferably, the unit cell parameter of the crystal structure of the inorganic material is 5. A method for preparing an inorganic material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) mixing a lithium source, a lanthanum source, a zirconium source, an aluminum source, an iron source, and a gallium source, adding a solvent, and ball milling to obtain a mixed slurry; (2) drying the mixed slurry obtained in step (1), and then roasting it, and then calcining it to obtain an inorganic material; wherein the calcination temperature is higher than the roasting temperature.
6. The method for preparing an inorganic material according to claim 5, characterized in that: In the step (1), the lithium source includes LiOH·H2O; the lanthanum source includes La2O3; the zirconium source includes ZrO2; the aluminum source includes Al2O3; the iron source includes Fe2O3; and the gallium source includes Ga2O3; And / or, in the step (1), the ball milling time is 3 to 5 hours; And / or, in the step (2), the calcination temperature is 600-700° C., and the calcination time is 1-2 h; And / or, in the step (2), the calcination temperature is 900-1000° C., and the calcination time is 2-7 hours.
7. Use of the inorganic material according to any one of claims 1 to 4 or the inorganic material prepared by the preparation method according to any one of claims 5 to 6, characterized in that: The inorganic material is used in lithium-ion batteries; And / or, the inorganic material is used for at least one of a solid electrolyte, a separator, a membrane coating, a positive electrode material coating layer or a negative electrode material ion conductor.
8. A diaphragm, characterized in that: The invention comprises the inorganic material according to any one of claims 1 to 4 or the inorganic material prepared by the preparation method according to any one of claims 5 to 6.
9. A method for preparing the diaphragm according to claim 8, characterized in that: The following steps are involved: 1) mixing the inorganic material, the binder and the solvent to obtain a slurry; 2) The slurry is coated on one side or both sides of a base film and dried to obtain a separator.
10. A lithium ion battery, characterized in that: The invention comprises the inorganic material described in any one of claims 1 to 4 or the inorganic material prepared by the preparation method described in any one of claims 5 to 6 or the diaphragm described in claim 8 or the diaphragm prepared by the preparation method described in claim 9.
